The Effect of Connecting, Organizing, Reflecting, Extending Learning Model Assisted by Audio-Visual on Mathematics Learning Outcomes - Dewi, Ni Kadek Veronika; Suarni, Ni Ketut; Japa, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of the Connecting, Organizing, Reflecting, extending (CORE) learning model assisted with audio-visual media on fourth-grade students' mathematics learning outcomes. The type of research is a quasi-experimental research design with a post-test only control group design. The population used in this study was the fourth-grade, with the samples used were IVB class with 34 students as the experimental group and IVA class with 36 students as the control group. The data collection method used is a test method with multiple choice objective test instruments. The obtained data is analysed by using descriptive statistical analysis and inferential analysis. The analysis results obtained were the average score in the experimental group given with the treatment of the CORE learning model assisted by audio-visual media amounted to 21,91. The control group that was not given the CORE learning model's treatment assisted by audio-visual media amounted to 14,00. The t-test analysis obtained count 21,547 and table 2,000 with db. = 68 at a significance level of 5%. With the criteria, count> table so that H0 is rejected and H1 is accepted. The difference scores between the experimental and control groups indicate that there is a significant influence in applying the CORE learning model assisted with audio-visual media in the mathematics learning outcomes of fourth-grade students.